2020
DOI: 10.1302/2046-3758.911.bjr-2020-0178.r1
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA in muscle regeneration and diseases related to muscle dysfunction in atrophy, cachexia, osteoporosis, and osteoarthritis

Abstract: MicroRNAs (miRNAs) are a class of small non-coding RNAs that have emerged as potential predictive, prognostic, and therapeutic biomarkers, relevant to many pathophysiological conditions including limb immobilization, osteoarthritis, sarcopenia, and cachexia. Impaired musculoskeletal homeostasis leads to distinct muscle atrophies. Understanding miRNA involvement in the molecular mechanisms underpinning conditions such as muscle wasting may be critical to developing new strategies to improve patient management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 75 publications
(104 reference statements)
2
19
0
Order By: Relevance
“… 32 , 33 miRNAs have been shown to be closely related to the progression and severity of OA. 34 , 35 Therefore, the regulatory mechanism underlying circSCAPER in OA was further explored, and we confirmed that circSCAPER directly binds to miR-140-3p. miR-140-3p isomiRs are abundantly expressed in cartilage, which is more effective than the original miR-140-3p annotated in miRBase 36 - 38 in human and murine chondrocytes, 39 suggesting the potential function of miR-140-3p in OA.…”
Section: Discussionsupporting
confidence: 52%
“… 32 , 33 miRNAs have been shown to be closely related to the progression and severity of OA. 34 , 35 Therefore, the regulatory mechanism underlying circSCAPER in OA was further explored, and we confirmed that circSCAPER directly binds to miR-140-3p. miR-140-3p isomiRs are abundantly expressed in cartilage, which is more effective than the original miR-140-3p annotated in miRBase 36 - 38 in human and murine chondrocytes, 39 suggesting the potential function of miR-140-3p in OA.…”
Section: Discussionsupporting
confidence: 52%
“…The teleost muscle is also an immunologically active organ, playing an important role against pathogens [ 71 ]. MicroRNAs are established modulators of muscle cell proliferation, differentiation, regeneration, and diseases [ 72 ]. Our miRDeep2 analysis identified 328 conserved mature miRNAs in lumpfish muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of our study is the combined approach in the RAAK and in the GARP study, thereby allowing analyses of the same circulating miRNAs in two independent study cohorts while including data from non-endstage OA patients. Previous studies have explored the potential of circulating miRNAs as biomarkers in OA [ 11 , 46 , 47 ]. However, many of such studies have taken a targeted approach.…”
Section: Discussionmentioning
confidence: 99%